Parental associations and education politics regarding disability: the case of Cyprus - Symeonidou, Simoni (International Journal about Parents in Education, 2023)
This paper is about parental associations and their impact on educational developments regarding the education of disabled children in Cyprus. It mainly comments upon parents’ conceptualisations of disabled children’s rights which guided their responses to education politics. The historical and interpretative nature of this paper is achieved by building arguments through interpreting qualitative data covering the period 1970-2007. Four periods associated with important developments were identified to facilitate understanding of parental involvement in politics: early forms of parental mobilization, parents’ groups acting as ‘non-pressure’ groups, parental power through networking and resolving issues of identity and power between parents’ pressure groups. The paper ends with a critical discussion of parental involvement in education politics in relation to the nature of parents’ associations which constitute this evolving pressure group.